2015
DOI: 10.1038/ijosup.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of brown adipose tissue research: integrating the old and new

Abstract: Renaissance of brown adipose tissue research: integrating the old and new JG GrannemanThe recent demonstration of active brown adipose tissue (BAT) in adult humans, along with the discovery of vast cellular and metabolic plasticity of adipocyte phenotypes, has given new hope of targeting adipose tissue for therapeutic benefit. Application of principles learned from the first wave of obesity-related BAT research, conducted 30 years earlier, suggests that the activity and/or mass of brown fat will need to be gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
0
4
0
2
Order By: Relevance
“…One cohort was evaluated in cross-section analysis and the other was evaluated before and after undergoing bariatric surgery. Obesity is one of the main factors contributing to low BAT glucose uptake in humans [23,48,70,71]. Upon reduction of body mass, BAT glucose uptake increases in association with both the attenuation of insulin resistance and reduction of systemic inflammation [48,54,70].…”
Section: Discussionmentioning
confidence: 99%
“…One cohort was evaluated in cross-section analysis and the other was evaluated before and after undergoing bariatric surgery. Obesity is one of the main factors contributing to low BAT glucose uptake in humans [23,48,70,71]. Upon reduction of body mass, BAT glucose uptake increases in association with both the attenuation of insulin resistance and reduction of systemic inflammation [48,54,70].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that thermogenic tissue is inversely related to body mass index and body fat percentage (Granneman, 2015;Peng et al, 2015;Vosselman et al, 2015).…”
Section: Role Of Adenosine In Thermogenesis During Obesitymentioning
confidence: 99%
“…In response to fasting, adipocyte lipolysis is mainly stimulated by β-adrenergic hormone norepinephrine (NE) and catalyzed sequentially by adipose triglyceride lipase (ATGL), hormone-sensitive lipase (HSL), and monoacylglycerol lipase (MGL) (1,5). During chronic cold exposure, lipolytic activation by NE leads to the upregulation of thermogenic gene program in brown adipose tissue (BAT) and the appearance of brown-like (beige) adipocytes in subcutaneous white adipose tissue (WAT) (6). A promising therapeutic concept for treating obesity and its associated disorders is through expanding the beige adipocyte population and thereby enhancing whole-body energy expenditure (7).…”
Section: Introductionmentioning
confidence: 99%